Graduation Book Information System Of Muhammadyah University Of Bengkulu - Fikri Agnesa Putra; Gunawan Gunawan; RG Guntur Alam; Yetman Erwadi (Penerbit Jurnal Indonesia, 2023)
A system is an entity consisting of two or more components that interact with each other to achieve a goal. Information means the result of a process that is organized, meaningful and useful to the person who receives it. Graduation is an activity for the inauguration ceremony of graduation, handing over diplomas, release, and returning students to parents and as a sign that students have completed their studies. The graduation book system is closely related to internal control issues and as a tool to monitor and protect company assets. Students register to submit to the study program staff with complete files, then the staff verifies whether it is complete or not. Make a list of graduation registrants for student names then submit them to the head of study program, then the head of study program directs to BAAK. BAAK analyzes and retypes then creates a judicial decree. Then the next stage is BAU as the graduation equipment committee to make a graduation book by re-distributing the google form to request data by registering so complicated, the author hopes by proposing a graduation book information system by making it easier for students as well as BAAK and BAU of the University of Muhammadiyah Bengkulu. The research objectives that the author wants to achieve are: Produce a graduation book system or application, providing convenience to students in obtaining web-based information. Research through case studies conducted on the Graduation Book Information System of the University of Muhammadiyah Bengkulu by conducting interviews and providing questionnaires to parties and through literature studies. System development methods use analysis (system requirement analysis), design (design), coding (code generation), testing (testing), database design. From this research, a Graduation Book System application was produced consisting of the main page, graduation candidate page, operator page and admin page. With the Graduation Book Information System, it can make it easier to access the system that has often experienced obstacles in viewing graduation information, such as graduation schedules and graduation requirements.